Demographic potential of sex-age structure as a factor of population dynamics - Vladimir N. Arkhangelskiy; Yuliya V. Zinkina; Sergey G. Shulgin (Статистика и экономика)
The study aims to assess the sex-age population structure in terms of its impact on the up-coming dynamics of natural increase and, consequently, on the general change in the population size. There are various approaches to assessing this influence, proposed and used by scientists who have studied this aspect of demographic dynamics. This article discusses a relatively simple indica-tor of the sex-age population structure, which allows estimating its future influence on the ratio of births to deaths, and on the natural population growth. The indicator proposed is the so-called demographic potential of the sex-age structure, which is the ratio of female population aged 10–39 to the population of both sexes aged 65 years and older. The number of births in the next 10–15 years largely depends on the size of the first one, while the number of deaths in this period depends on the size of the second one.Before using the demographic potential of the sex-age structure to forecast the dynamics of natural population growth, a retrospective assessment of the relation of this potential with subse-quent natural population growth should be carried out for some particular time point in the past. We chose the sex-age structure of the mid-2000s and the natural increase (per 1000 population) in 2000–2015 for such assessment, accounting for 201 countries. The high value of the correlation coefficient (0.815) indicates that the current sex-age structure and its demographic potential can be used (with varying degrees of conditionality, of course) to forecast the future dynamics of natural growth. In turn, the size of the demographic potential of the sex-age structure of the population depends on the preceding levels of fertility and mortality.An assessment of the demographic potential of the sex-age population structure in mid-2015 for 201 countries of the world showed that in a number of countries in Asia and Africa the value of this potential exceeds 10, so significant natural population growth is highly probable there in the next 10–15 years. Meanwhile, in a number of European countries the value of this potential is less than 1 (i.e., the population aged 65 years and older is larger than the female population aged 10–39 years), which is likely to result in a very small natural increase (in case of a favorable mode of pop-ulation reproduction) or even a natural decline.